DEPOSIT POLICY OF COMMERCIAL BANKS - Ismoilov Diyorbek Islom o`g`li (PEDAGOGS, 2024)
Abstract. The article is based on the analysis of the deposit policy of commercial banks and its effective implementation, as well as the analysis of the circumstances that have a negative impact on the further increase of economic importance-dedicated to issues such as creating conditions, expanding the possibilities of using the mobile application, activating the processes of introducing modern contactless payment methods, putting deposit services into practice. The deposit policy of commercial banks and practical proposals for its effective implementation and further increase of their economic importance are given.